Women's clothing, ornaments and cosmetics in the Laghouat region during the 19th century - djadj, Fatima (The Algerian Historical Journal, 2026)
The article is a historical, social and cultural study, as it focuses on one of the aspects of social and cultural life in the Laghouat region, and specifically studies the dress, jewelry and adornment tools of women in the Laghouat region during the 19th century AD. As it reflects important aspects of the culture and thought of this society, where women took care of their appearance, they dressed in fashion that reflects the society's adherence to the teachings of its religion, and its preservation of its customs and traditions. In addition to women's interest in highlighting their beauty, by wearing different pieces of jewelry, to fix their clothes and to decorate as well. And the use of tools and natural materials to adorn it, such as henna, kohl and toothpicks, was able with simple tools to preserve its beauty and brilliance.